Pahang allocates RM8.2m to assist athletes to become entrepreneurs NSTTV - T.N., Alagesh (New Straits Times Press (M) Bhd., 2022)
KUANTAN: The Pahang government has set aside RM8.2 million to assist some 1,000 athletes in the state who are interested in entrepreneurship.